Веселый солдат: [повесть, рассказы] / Виктор Астафьев - Астафьев Виктор Петрович (Мастер серия, 2000)
Экземпляры: аб. (2001) / Инвентарный номер: 43430 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 91 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)6-4